Karakteristik Perkembangan Anak Usia Dini Menurut Para Tokoh - Yuli Umro'atin Yuli (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2022)
Abstract Early childhood has distinctive/unique characteristics, both physically, psychologically, socially, morally and so on. Childhood is also the most important period of his life. Because childhood is a time of foundation formation and personality that will determine the next child's experience. Santrock stated that early childhood development includes aspects of physical, cognitive, socio-emotional development, social context, morals, language, self-identity, and gender. Kail and Reese explained that the scope of early childhood development includes the development of independence, morals, social, language, physical, and cognitive. Bukatko and Daehler stated that early childhood development includes brain development, motor skills, physical, perception, language, cognitive, intelligence, emotion, self-concept, values, and gender. Johnston and Halocha stated that early childhood development includes social, emotional, physical, spatial, cognitive, and language development. Berk stated that the scope of child development includes physical, cognitive, intelligence, language, emotional, social and moral development.